2017
DOI: 10.3233/jad-170136
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Detection of Gray Matter Neuropathology in the 3xTg Mouse Model of Alzheimer’s Disease with Diffusion Tensor Imaging

Abstract: Abstract.A diagnosis of Alzheimer's disease (AD), a neurodegenerative disorder accompanied by severe functional and cognitive decline, is based on clinical findings, with final confirmation of the disease at autopsy by the presence of amyloid-␤ (A␤) plaques and neurofibrillary tangles. Given that microstructural brain alterations occur years prior to clinical symptoms, efforts to detect brain changes early could significantly enhance our ability to diagnose AD sooner. Diffusion tensor imaging (DTI), a type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 59 publications
(89 reference statements)
1
20
1
Order By: Relevance
“…The latter results were highly consistent with those of Shu et al (2013) (Shu et al, 2013). In the triple transgenic (3xTgFAD) mouse model, reduced FA and AD was measured only in the hippocampus (Snow et al, 2017). Results similar to those obtained here were reported by Sun et al, who observed reduced relative anisotropy along with reduced AD and increased RD in the Tg2576 mouse model (Sun et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…The latter results were highly consistent with those of Shu et al (2013) (Shu et al, 2013). In the triple transgenic (3xTgFAD) mouse model, reduced FA and AD was measured only in the hippocampus (Snow et al, 2017). Results similar to those obtained here were reported by Sun et al, who observed reduced relative anisotropy along with reduced AD and increased RD in the Tg2576 mouse model (Sun et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…The ADC levels were ambiguous, the only differences being the higher values shown by the 3xTg‐AD at 7‐mo in both the hippocampus and cortex. No statistical differences in the mean diffusivities were observed either in other studies using the 3xTg‐AD mouse model although a tendency to increased ADC values in 3xTg‐AD mice could be noticed at 12–14‐mo in the cortex region . Thus, it was likely that neither significant inflammation processes nor vasogenic edemas occurred .…”
Section: Discussionmentioning
confidence: 67%
“…In fact, this is not a good model for causing vasogenic edema as this pathology is related to cerebral amyloid angiopathy (CAA) and the 3xTg‐AD does not develop it . Analysis of other DTI neurodegeneration related parameters like fractional anisotropy or axial and radial diffusivities may provide additional information about microstructural anomalies, which may be worth considering to include them in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these findings were not confirmed in ex-vivo DTI measurements, which revealed no loss in white matter integrity (Harms et al, 2006 ), raising questions about the source of the signal actually lost upon formalin fixation. More recently, DTI abnormalities have been confirmed in multiple white matter tracts as well as in the hippocampus in different mouse models for AD (Kerbler et al, 2013 ; Snow et al, 2017 ) and imaged in vivo at different field strengths, for example, 7 T (Whittaker et al, 2018 ) or 11.7 T (Zerbi et al, 2013 ). Further investigation of the APP model has confirmed abnormalities in DTI metrics both in gray and in white matter (Bitner et al, 2012 ; Qin et al, 2013 ; Shu et al, 2013 ; Shen et al, 2018 ; Liu L. et al, 2020 ).…”
Section: Applications To Models Of Neurodegenerative Diseasesmentioning
confidence: 99%